PENGARUH EFISIENSI BIAYA OPERASIONAL DAN LEVERAGE KEUANGAN TERHADAP NILAI PERUSAHAAN BATU BARA YANG TERDAFTAR DI BEI PERIODE 2021-2024 - Anggun Salsabila; Ajeng Tita Nawangsari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to examine and analyze the influence of Operational Cost Efficiency and Financial Leverage. This research uses a quantitative research method, with secondary data obtained from the companies' annual financial statements. The population and sample of this study are coal companies' financial statements listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The sampling technique used is purposive sampling, resulting in 40 data samples. The results of this study indicate that Operational Cost Efficiency affects the company's value, whereas Financial Leverage does not affect the company's value.